“Prevalencia de parasitismo intestinal en escolares de 5 a 11 años de la unidad educativa del milenium del cantón penipe” - Barona Rodriguez, Jorge Washington (2018)
This project was mde in the Millenium educative unit of Penipe canton in the period October 2017 – March 2018. The population was taken as 389 legally enrolled students, obtaining a sample of 133 students who met inclusion criteria, aimed at boys and girls from first to seventh grade of basic education. It was made a study descriptive, quantitative – qualitative of the study variables, observational methodology, cross – section and mixed approach was made in the estudents of Millennium educative unit, which objective was determine and classify the prevalence of intestinal parasitosis, according to the causal agent through the Coproparasite test, establishing the global prevalence in the individuals included in the study population. For its purpose, were developed study indicators through the described methodology, it was done through the Microsoft excel computer package, together with the coproparasite technique, obtaining that 54% of children didn´t have parasites, while 36% have parasites, with a predominance of the feminine gender in 55% and in 45% the masculine one, being the group of ages of greater incidence the one of eigth to ten years with 54%, followed of five to seve years with a 34%. E. coli has been identified as the main etiological agent with 48% and E. histolytic with 42%. And it is recommended to give continuity to studies related to the topic given in order to reduce this incidence in rural populations.